The Effect of Financial Performance and Firm Size on Firm Value with CSR as a Moderating Variable - Muh. Farhan Fatkur Rochman; Jannati Tangngisalu; Andi Agus (Golden Ratio of Auditing Research, 2026)
This study investigates the influence of financial performance and firm size on firm value, with Corporate Social Responsibility (CSR) as a moderating variable, focusing on manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange from 2021 to 2023. The relevance of this research lies in addressing the inconsistent findings in prior studies regarding how financial indicators and firm characteristics impact value creation in stakeholder-oriented business environments. Using a quantitative approach, the study employed purposive sampling to select 29 companies that consistently published financial and sustainability reports during the study period, resulting in 87 panel data observations. Panel data regression and Moderated Regression Analysis (MRA) were conducted using EViews 13 software. The findings reveal that financial performance, as measured by Return on Assets (ROA), and firm size significantly affect firm value, as measured by Price to Book Value (PBV). Furthermore, CSR effectively moderates the relationship between financial performance and firm value, but does not significantly moderate the effect of firm size on firm value. These results suggest that while profitability enhances firm value, its credibility and impact are further strengthened when aligned with social responsibility efforts. This study contributes to the growing literature on corporate sustainability and offers strategic insights for managers aiming to optimize both financial and social dimensions in enhancing firm valuation.